Mechanism of NLRP3 inflammasome intervention for synovitis in knee osteoarthritis: A review of TCM intervention - Han, Xianfu; Lin, Demin; Huang, Weiwei; Li, Dingpeng; Li, Ning; Xie, Xingwen (Frontiers in Genetics, 2023)
Objective: This paper briefly reviews the structure and function of NLRP3 inflammasomes, signaling pathway, relationship with synovitis in KOA, and intervention of traditional Chinese medicine (TCM) in NLRP3 inflammasomes as a means to improve its therapeutic potential and clinical application. Method: Literatures about NLRP3 inflammasomes and synovitis in KOA were reviewed to analyze and discuss. Result: NLRP3 inflammasome can activate NF-κB mediated signal transduction, which in turn causes the expression of proinflammatory cytokines, initiates the innate immune response, and triggers synovitis in KOA. The monomer, TCM decoction, external ointment, and acupuncture regulating NLRP3 inflammasomes are helpful to alleviate synovitis in KOA. Conclusion: The NLRP3 inflammasome plays a significant role in the pathogenesis of synovitis in KOA, TCM intervention targeting the NLRP3 inflammasome can be a novel approach and therapeutic direction for the treatment of synovitis in KOA.